KEMAMPUAN SISWA KELAS X UPW SMK NUSATAMA PADANG DALAM MENGGUNAKAN SHIJISHI - selviana dewi; Hendri Zalman; Damai Yani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2018)
This research discusses about shijishi student class X Unit Tour SMK Nusatama Padang , the purpose of this research is to know about students skill of shijishi student class X Unit Tour SMK Nusatama Padang.   Type of this research is quantitative research, using descriptive method. The population is 37 people. Sample in this reserch is students class X Unit Tour SMK Nusatama Padang which amout 37 people. Whith is dertemined by using the total sampling technique. Data of this research is shijishi test score.            Based and the result of the research test can be concluded some of things that is. First, students shijishi ability class X Unit Tour SMK Nusatama Padang with an average value 52,25. Second, from of the indicators that have tested can be concluded that the students shijishi ability class X Unit Tour SMK Nusatama Padang. There is no stongest indicator , because on both of indicators. There are average value which is almost some that is on indicator I (identity the using of shijishi kore, sore, are) which average value 53,60, and for second indicator (identity the using of shijishi koko, soko, asoko) which average value 50,90. Third, shijishi ability included in class less classification.Keywords: Ability, Shijishi